I am who I am because I am a sister: exploring sister relationships in middle adulthood - Ricklefs, Tonya Kay (Kansas State University, 2015)
Sibling relationships have often been studied with the goal of understanding the sibling influence on development of an individual. With the focus on development, research has often been limited to the time of life between the ages of birth to 18. Sibling research in adulthood has often been limited to examining siblings’ interactions in a particular context. Most of the research has examined siblings dealing with caregiving, family businesses, finances, or parental treatment. How siblings feel about their relationship, how the relationship has enhanced their lives, and what meaning individuals ascribe to that relationship through their lifetime has been understudied. This study focused on the meaning ascribed to a relationship between sisters by those in the relationship as well as the importance of sisterhood to the individual’s identity or perception of who they are because of the relationship. Participants responded to questions designed to gather information about what it means to them to be a sister in middle adulthood. The sisters indicated that the relationship held meaning for them though out their adult life. Parents were found to have influenced the relationship. In addition the sister relationship impacted the development of a sisters identity in multiple ways. For most sisters, they could not imagine who they would have become without the influence of their sisters.
Keywords: Sister; Middle adulthood; Relationship; Communication; Parental influence; Meaning; Individual & Family Studies (0628); Social Psychology (0451)